PENDAPATAN DAN KELAYAKAN PADI SAWAH (Oryza Sativa L.) DI KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN (Income And Feasibility Of Lowland Rice Farming (Oryza Sativa L.) In Lubuk Alung Sub-District, Padang Pariaman District) - LEOVITA, ANGELIA; SYAHRIAL, SYAHRIAL; NURHADINA, NURHADINA (Universitas Mulawarman (University of Mulawarman), 2023)
Rice is a food crop in the agricultural sector, which is an ingredient in the form of rice that is consumed by the majority of the Indonesian population, as well as being a source of income for farmers. This research aims to 1) Describe the characteristics of lowland rice farmers 2) Analyze the income of lowland rice farming 3) Analyze the feasibility of lowland rice farming. The technique for taking respondents used in this research was proportional random sampling with a total of 44 respondents. The data analysis method used is qualitative descriptive analysis and income analysis and feasibility analysis (BEP and R/C). The results of the research show that the characteristics of rice farmers in Lubuk Alung District, Padang Pariaman Regency based on gender are male-dominated 68.18 percent, respondents' age ranges from 38-43 years at 36.36 percent, elementary school education 40.91 percent, farming experience 10- 13 years of 47-73 percent, with a farmer's land area of 0.46-0.66 Ha of 47.73 percent, own land ownership status of 100 percent. The average income of rice farmers in Lubuk Alung District is IDR. 5,643,883.68 per planting season. The feasibility of lowland rice farming in Lubuk Alung sub-district is feasible because it has an R/C value of 1.91, B/C 1.01 and production and price are above the BEP value.